Datasphere and SAP: How Data Integration Can Drive Business Value - Arunkumar Pasumarthi,; Balamuralikrishnan Anbalagan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
At the time of the relevance of information and data as the foundation of current strategic business making, it becomes important to connect unrelated systems to draw relevant and practical business intelligence (Walha et al., 2024; Egbert & Ulbricht, 2024). This paper discusses SAP-Datasphere collaboration, and it emphasizes the revolution entering enterprise activities; modern data integration architecture. It considers the feasibility of a standardized data environment through consideration of the functionalities of the systems involved, mode of integration and relative deployment rates (Li et al., 2024). Using the combination of qualitative approach and thematic analysis, the research herein depicts a systematic report on the effect SAP Datasphere has on enhancing the organizational performance, scalability, and regulatory compliance of companies (Zhou et al., 2024). It also involves compilations of comparative tables and visual presentations which illustrate metric of performance, ROI and automation metrics (Visani et al., 2024). The results show that businesses that use SAP Datasphere realise greater flexibility in operations and determinable competitive edge in data-intensive markets. Finally, the paper will provide a set of effective recommendations to every enterprise willing to achieve significant business value using advanced data integration (Chatterjee et al., 2024; Gao & Sarwar, 2024).
Keywords: SAP; Datasphere; Data Integration; Business Value; Digital Transformation; Enterprise Analytics